Simbiosis Mutualisme Pada Transakasi Jual Beli Rumput Laut Dalam Perspektif Marketing Syariah (Studi Kasus Pada Petani Desa Pattiro Sompe Kecamatan Sibulue Kabupaten Bone) - Abd Rahman; H. Ahmad Abdul Mutalib; Hartas Hasbi (Institut Pendidikan Alfatah Mataram, 2025)
This research aims to examine the mutualistic symbiosis in seaweed buying and selling transactions from the perspective of Islamic marketing. The subjects of the study are seaweed farmers, utilizing qualitative data analysis techniques with a descriptive approach. The findings indicate that the community of Pattiro Sompe Village, located in Bone Regency, South Sulawesi, is known for its seaweed production, which operates through a mutualistic symbiosis system between farmers and buyers. This system benefits both parties, as farmers gain profits from their harvests while buyers acquire quality raw materials. The study analyzes the mutualistic symbiosis in these transactions, highlighting principles such as mutual consent, honesty, fairness, and commitment. Specifically, the transactions are conducted with mutual consent between farmers and buyers, both parties demonstrate honesty, the price of seaweed is determined based on mutual agreement, and both farmers and buyers are committed to fulfilling their obligations. Consequently, the mutualistic symbiosis in seaweed transactions in Pattiro Sompe Village serves as an example of the application of Islamic marketing in daily life, providing benefits for both farmers and buyers